2003
DOI: 10.1086/367686
|View full text |Cite
|
Sign up to set email alerts
|

Hubble Space TelescopeWFPC2 Morphologies ofK‐selected Extremely Red Galaxies

Abstract: We selected 115 extremely red objects (EROs) from deep Hubble Space Telescope (HST) WFPC2 archive data combined with ground-based K-band images, with (F814WÀK s ) ! 4, K-band signal-to-noise ratio !5, and a median limiting K s magnitude of $18.7, over a corresponding area of 228 arcmin 2 , for a morphological study of the ERO galaxy population. The survey covered a total of $409 arcmin 2 over 77 separate WFPC2 fields. This is the first complete sample of bright EROs with high-resolution HST morphologies. From … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
110
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(126 citation statements)
references
References 47 publications
15
110
1
Order By: Relevance
“…Note that we have not compared with field counts derived from other colors (e.g., IÀK or IÀH ), since they may bias toward later type galaxies with prolonged star formation (McCarthy et al 2001;Yan & Thompson 2003 The literature surveys cover wide, random areas and should therefore be representative of the ERO counts in the general field. The field counts agree well with each other, except for the counts in the Chandra Deep Field South by Scodeggio & Silva (2000), which are consistently lower than the other.…”
Section: Surface Density Of Erosmentioning
confidence: 99%
“…Note that we have not compared with field counts derived from other colors (e.g., IÀK or IÀH ), since they may bias toward later type galaxies with prolonged star formation (McCarthy et al 2001;Yan & Thompson 2003 The literature surveys cover wide, random areas and should therefore be representative of the ERO counts in the general field. The field counts agree well with each other, except for the counts in the Chandra Deep Field South by Scodeggio & Silva (2000), which are consistently lower than the other.…”
Section: Surface Density Of Erosmentioning
confidence: 99%
“…At brighter levels, K < 17.5, we find a smaller percentage <20% of dusty EROs (Väisänen & Johansson 2004, hereafter Paper I). Recent HST morphological studies have complicated the picture somewhat by finding large fractions of disk galaxy EROs (Yan & Thompson 2003;Moustakas et al 2004;Gilbank et al 2003). In addition to morphological, spectroscopic, or colour property methods, the separation of dusty and early type EROs can also be done using detections at longer wavelengths, where ellipticals are not expected to radiate much.…”
Section: Introductionmentioning
confidence: 99%
“…Strategies to distinguish the fraction of different extragalactic ERO types include near-infrared photometric classification (Pozzetti & Mannucci 2000;Mannucci et al 2002;Martini 2001;Hempel et al 2003), morphological tests (Yan et al 2000;Yan & Thompson 2003;Gilbank et al 2003;Moriondo et al 2000), and an increasing number of spectroscopic discriminators (Cimatti et al 1999(Cimatti et al , 2002aSmith et al 2001). Near-infrared spectroscopy of 9 EROs (R − K > 5 and K < 19.0) by Cimatti et al (1999) showed neither strong emission lines nor continuum breaks.…”
Section: Introductionmentioning
confidence: 99%